Bacteriological and Physicochemical Assessment of Abattoir Wastewater and Its Contaminated Soils in Adamawa State, Nigeria - Pola, Bristone James (Darul Yasin Al Sys, 2025)
Water and soil contamination by abattoir waste is a growing environmental concern worldwide. Abattoir wastewater is emerging as a significant contributor to environmental degradation, particularly in Nigeria and the developing countries. This research was aimed at assessing the Bacterial load and physicochemical properties of abattoir wastewater and its contaminated soils in Adamawa State, Nigeria. Wastewater/effluent and soil samples were collected from three (3) abattoir sites in three senatorial district of the State. Both samples were transported to the Microbiology Laboratory for analysis. The bacterial load and the physicochemical parameters were determined from both samples using standard methods of examination of wastewater and soil. All data obtained were subjected to statistical analyses using analysis of variance (ANOVA) IBM version 28. The total counts for the contaminated waste water ranged from 5.10 ± 1.2 - 7.90 ± 1.4 ×105 cfu/mL, while the contaminated soil ranged from 5.06 ± 1- 7.90 ± 1.5 ×105 cfu/g. Most of the physicochemical parameters were within the permissible limits except conductivity values which were above the acceptable limits of 1000 (uS/cm), biological oxygen demand (BOD) (above 50 mg/l) and total suspended solids (TSS) (1000 mg/l) of the wastewater. Physicochemical properties of soil contaminated with abattoir effluent showed that the soils happened to be mainly loamy and sand indicating that the effluent had no effect on the soil textural class. In terms of the chemical properties, pH values were low on the effluent contaminated soils; most of the parameters analyzed had higher values in the contaminated soils than the control. The highest values of the physicochemical parameters for pH, organic carbon, total nitrogen content, water holding capacity of contaminated soil were within the ranges of (6.06 -6.89), (1.078 - 6.89), (1.858 – 1.943), (0.094 -0.102), (10.000 - 12. 200) and the textural class was sandy loamy. The presence of high microbial load found in wastewater and contaminated soils and the high physicochemical properties observed can be attributed to high organic waste released by these abattoirs. These affect human health by causing diarrhea, urinary tract infections and can subsequently alter the immediate environment.